Achieving best management practices in an oil palm plantation at tropical peatland: a gap analysis - Richard, Adesiji Adeolu; Mohammed Ali, Thamer Ahmed; Nik Daud, Nik Norsyahariati; Mustapha, Sa'ari; Sayok, Alexander Kiew; Padfield, Roryd; Evers, Stephanie (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Despite the economic gains recorded in the oil palm industry, the industry has faced serious challenges in terms of sustainability. Non-adherence to the best management practices has been blamed for such challenges and mitigating the resultant negative results is inevitable. In this work, a framework consisting of site management and best management practices which analyzes the gaps between the two practices was developed and conclusions on possible divergence drawn. Literature review and interviews to gather opinions from the experts and practitioners in the industry were used. In conclusion, there is no proper adherence to the recommended best management practices.